Pathogenicity of local isolates of Erysipelothrix rhusiopathiae serotypes 1, 2, 6, ! 1, 12, and type N in mice and pigs - Chotiah, Siti (Indonesian Journal of Animal and Veterinary Sciences, 1998)
Six local isolates of Erysipelothrix rhusiopathiae of serotypes 1, 2, 6, 11, 12 ; ?,.;d type N isolated from the tonsil of healthy pigs at Kapuk, Jakarta, slaughter house were examined for their pathgb-;ucity for mice and pigs . Forty-two groups of mice, each contains ten mice and twenty-one pigs divided into seven groups were used as experimental animals. Isolates of serotype 1, 2, 6, 11, 12, and type N were pathogen for rnil.e with LDSO of 10", 102.", 10°6 ,103.° , 10 32 and 105A colony forming unit (C .F .U .), respectively. All (100%) pigs inoculated with isolate of serotype 1 and 33.3% pig inoculated with isolate of serotype 2 were induced general urticarial lesions with depression, anorexia and followed by death. One of three (33.3%) pig inoculated with isolate of serotype 6 was induced generalized urticarial lesions without any other clinical signs. Isolates of serotype 6, 11, 12, and type N were capable of inducing localized urticarial lesions in two out ~f three (66.7%), all (100%), two out of three (66.7° n all (100%) pigs, respectively . All pigs in control uninoculated Key words : Erysipelothrix rhusiopathiae, pathogenicity, mice, pigs